Analysis of the Impact of Tax Revenues on Accountability: Practical Experience Across Central Asia - Burhonov Azizbek; Heryana, Toni; Islami , Imas Nurani (International Journal of Economics, Business and Innovation Research, 2026)
This study sought to examine the effect of tax revenues on government accountability, specifically focusing on the five countries that make up the Central Asian region. This includes Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan. This study will focus on the aforementioned countries with regard to the past five years, comparing the tax revenues collected on their effect on the fiscal institutions' level of transparency. From the study, it is clear that an increased level of tax revenues collected does have a positive effect on the level of government transparency but with varying degrees that are determined by the political structure of the institutions. The study makes a theoretical contribution to the understanding of fiscal accountability in transition economies, as well as practical suggestions to policymakers who wish to reinforce the link between revenue generation and responsible governance.